Watermelon rind based adsorbents for the removal of water pollutants: a critical review - Onyango, Collins; Nyairo, Wilfida; Tchieta, Gerard P.; Shikuku, Victor O. (Frontiers in Environmental Chemistry, 2025)
The potent of watermelon based adsorbent for the elimination of various pollutants from water was reviewed. This study shows that watermelon-based adsorbents offer a cost effective and environmentally friendly adsorbent for the removal of many pollutants including dyes, heavy metals and nutrients. The main functional groups responsible for the binding properties of raw watermelon rind are the hydroxyl (–OH), carboxyl (–COOH), carbonyl (-C=O-) and amines (-NH2). Equilibrium adsorption data largely followed the Langmuir isotherm, whereas the kinetic data for both dyes and heavy metals mostly fitted to the pseudo-second order kinetic model. This notwithstanding, very few studies reported the use of natural wastewaters to gain insight into the potential for real world application. Again, the review noted an overreliance on the isotherms, kinetic and thermodynamic data in predicting the mechanism of adsorption. Nonetheless, watermelon rind based adsorbents offer an effective removal means for many pollutants, calling for further exploration, with future research likely to focus on overcoming the aforementioned limitations.